Method for strengthening magnesium sulfate crystallization through magnetic field

By using an external variable magnetic field and programmed cooling technology during the magnesium sulfate crystallization process, the problems of low recovery rate and high energy consumption in magnesium sulfate crystallization have been solved, and the efficient production of high-purity magnesium sulfate has been achieved.

CN120964855APending Publication Date: 2025-11-18LANZHOU UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510973019.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-15
Publication Date
2025-11-18

AI Technical Summary

Technical Problem

Existing technologies for magnesium sulfate crystallization suffer from low recovery rates, high energy consumption, and insufficient crystal purity, making it difficult to meet the requirements for high-purity magnesium sulfate fertilizer. The application of magnetic fields in magnesium sulfate crystallization has not yet been effectively utilized.

Method used

By applying an external variable magnetic field during the crystallization process of magnesium sulfate solution, combined with programmed cooling and seed crystal addition, the magnetic field strength and stirring method are controlled to promote ion migration and water molecule arrangement, thus achieving efficient precipitation of magnesium sulfate crystals.

Benefits of technology

This method improves the recovery rate and purity of magnesium sulfate crystals, reduces crystallization energy consumption, and enables the industrial production of high-purity magnesium sulfate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120964855A_ABST
    Figure CN120964855A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of chemical crystallization, in particular to a method for strengthening magnesium sulfate crystallization through a magnetic field, which comprises the following steps: S1, placing 100.00-110.00 g of deionized water in a three-mouth beaker, heating to 60-80 DEG C, adding 40.00-50.00 g of anhydrous magnesium sulfate solute, stirring and dissolving for 10-30 minutes at the temperature of 60-80 DEG C and the speed of 100-120 r / min until the magnesium sulfate solute is completely dissolved to obtain a magnesium sulfate solution with the mass concentration of 28-33%; s2, placing the completely dissolved magnesium sulfate solution obtained in the step S1 in an external variable magnetic field, stirring at the same time, controlling the cooling mode and the seed crystal addition amount, and promoting magnesium sulfate to be separated out in the form of MgSO4. 6H2O crystals; and S3, filtering solid and liquid obtained after crystallization for multiple times to obtain wet crystals, and carrying out vacuum drying to obtain MgSO4. 6H2O dry crystals. Under the action of the magnetic field, the migration rate of Mg < 2 + > and SO4 < 2-> ions in the magnesium sulfate solution is increased, the crystallization activation energy is reduced by 2-10 kJ / mol, and the overall energy consumption is reduced by 15%-22% compared with that of traditional evaporative crystallization. The crystallization product is MgSO4. 6H2O, the crystal recovery rate reaches 35%-64% and is increased by 40%-156% compared with the traditional magnetic field-free crystal theory recovery rate 25%, and the crystal purity is larger than or equal to 99.5%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of chemical crystallization technology, specifically to a method for strengthening magnesium sulfate crystallization using a magnetic field. Background Technology

[0002] Magnesium sulfate, as an important inorganic chemical raw material, has wide applications in agriculture, medicine, and other fields. As a high-quality magnesium fertilizer, magnesium sulfate is of great significance to crop growth. Magnesium is a core component of chlorophyll and promotes plant photosynthesis. In soil, magnesium sulfate can regulate pH, improve soil structure, enhance aeration and water retention, and create a favorable rhizosphere environment. It can also improve crop resistance to stress, enhancing their ability to withstand drought, low temperatures, and pests and diseases. Furthermore, it helps improve the quality of agricultural products, such as increasing fruit sweetness and enhancing color. According to the 2023 National Land Change Survey, China's arable land area is approximately 128 million hectares. If 10 kg of magnesium fertilizer is applied per hectare, approximately 1.28 million tons of magnesium fertilizer are needed for arable land alone.

[0003] Currently, the industrial crystallization of magnesium sulfate (such as MgSO4·6H2O) mainly adopts traditional evaporation crystallization or cooling crystallization technology. Supersaturation is achieved through evaporation or cooling, thereby precipitating magnesium sulfate crystals. However, based on the solubility characteristics of magnesium sulfate, the theoretical recovery rate is only about 25%, which is low. Evaporation crystallization is energy-intensive, accounting for about 60% of the total energy consumption, while natural cooling crystallization is slow and has low crystallization efficiency. In addition, the purity of crystals obtained by traditional evaporation or cooling crystallization is low (below 95%), which is difficult to meet the requirements of high-purity magnesium sulfate for biological magnesium sulfate fertilizer.

[0004] To address these issues, existing technologies attempt to improve crystallization by optimizing cooling rates and adding seed crystals, but these methods do not address the microscopic mechanisms of ion migration and molecular arrangement, resulting in limited effectiveness. While magnetic fields, as clean and controllable physical fields, have been proven to influence the trajectories of charged particles in solution and the hydrogen bond structure of water molecules, their application in magnesium sulfate crystallization remains technologically limited. There is a lack of understanding of how magnetic field strength and cooling methods affect crystal morphology, purity, recovery rate, and energy consumption during the crystallization process, and industrial-scale scaling is difficult to achieve. Summary of the Invention

[0005] The purpose of this invention is to address the problems existing in the prior art by providing a method for strengthening magnesium sulfate crystallization through a magnetic field, thereby solving the problems existing in the background art.

[0006] To achieve the above objectives, the present invention provides the following technical solution:

[0007] A method for enhancing magnesium sulfate crystallization using a magnetic field, characterized by comprising the following steps:

[0008] S1: Place 100.00-110.00g of deionized water in a three-necked beaker and heat to 60-80℃. Add 40.00-50.00g of anhydrous magnesium sulfate solute and stir at 60-80℃ and 100-120r / min for 10-30min until the magnesium sulfate solute is completely dissolved to obtain a magnesium sulfate solution with a mass concentration of 28%-33%.

[0009] S2: Place the completely dissolved magnesium sulfate solution obtained in S1 in an external variable magnetic field, while stirring, controlling the cooling method and the amount of seed crystals added, to promote the precipitation of magnesium sulfate as MgSO4·6H2O crystals.

[0010] S3: After crystallization, the solid and liquid are filtered multiple times to obtain wet crystals, which are then dried under vacuum to obtain dry MgSO4·6H2O crystals.

[0011] Furthermore, in S1 and S2, the stirring methods in the high-temperature dissolution stage and the magnetization cooling crystallization stage include mechanical stirring, magnetic stirring, or ultrasonic stirring.

[0012] Furthermore, in S2, the strength of the external variable magnetic field is 100-3000 Gs, the magnetic field is a static magnetic field, the magnet is made of neodymium iron boron material, and the magnitude of the magnetic field is controlled by adjusting the spatial position of the N and S poles of the magnet.

[0013] Furthermore, in S2, the controlled cooling method adopts programmed cooling, with the cooling rate controlled at 1℃ / 10min and 1℃ / 1min respectively. The temperature is reduced from 60-80℃ to 40-45℃ through programmed cooling, and seed crystals are added at the same time, and then the temperature is further reduced to 20-25℃. The total cooling time is 60-600min.

[0014] Furthermore, in S2, the added seed crystals are MgSO4·6H2O particles with a particle size range of 20–100 μm and a purity of 99.5% or higher, and the amount added is 0.5%–1% of the mass of the magnesium sulfate solution.

[0015] Furthermore, in S3, the solid-liquid separation after crystallization is carried out by vacuum filtration, with a vacuum level of 0.060 to 0.085 MPa, and filtration is performed 2 to 4 times.

[0016] Furthermore, in S3, the drying is carried out using vacuum drying, with the drying temperature controlled at 30-45°C, the pressure controlled at 1-10 kPa, and the drying time controlled at 12-24 h, until the weight is constant and the weight loss is ≤0.1%.

[0017] Compared with the prior art, the beneficial effect of the present invention is that it increases the Mg content in magnesium sulfate solution through the action of a magnetic field. 2+ With SO4 2-The increased ion migration rate promotes ion diffusion to the seed crystal surface and induces the ordered arrangement of water molecules, reducing the solvation energy of hydrated ions and lowering the crystallization activation energy by 2–10 kJ / mol. Overall energy consumption is reduced by 15%–22% compared to traditional evaporation crystallization. The crystallized product is MgSO4·6H2O, with a crystal recovery rate of 35%–64%, which is 40%–156% higher than the theoretical recovery rate of 25% for traditional non-magnetic field crystals, and the crystal purity is ≥99.5%. Attached Figure Description

[0018] Figure 1 This is a schematic diagram of the magnesium sulfate crystals (MgSO4·6H2O) in this invention.

[0019] Figure 2 This is a morphology diagram of magnesium sulfate crystals (MgSO4·6H2O) used in this invention. Detailed Implementation

[0020] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0021] Example 1

[0022] 100.11 g of deionized water was placed in a three-necked flask and heated to 80 °C. 48.06 g of anhydrous magnesium sulfate was added, and the solution was stirred at 80 °C and 100 rpm for 30 min to dissolve, yielding a magnesium sulfate solution. The completely dissolved magnesium sulfate solution was placed in an external magnetic field, simultaneously stirred and subjected to programmed cooling. The magnetic field strength was 300 Gs, the rotation speed was 100 rpm, and the programmed cooling was set to 1 °C / 10 min, gradually reducing the temperature from 80 °C to 25 °C. When the temperature reached 45 °C, 1.03 g of MgSO4·6H2O seed crystals were added. During the cooling process from 45 °C to 25 °C, a large amount of crystals precipitated, with a crystallization time of 12 h. After crystallization, solid-liquid separation was performed by vacuum filtration at a vacuum level of 0.060 MPa, and the solution was filtered twice. The filtered crystals are then vacuum dried at a temperature of 35°C and a pressure of 5 kPa for 15 hours until the weight is constant, thus obtaining dry crystals.

[0023] Example 2

[0024] 100.10 g of deionized water was placed in a three-necked flask and heated to 80 °C. 48.09 g of anhydrous magnesium sulfate was added, and the solution was stirred at 80 °C and 100 rpm for 30 min to dissolve, yielding a magnesium sulfate solution. The completely dissolved magnesium sulfate solution was placed in an external magnetic field, simultaneously stirred and subjected to programmed cooling. The magnetic field strength was 300 Gs, the rotation speed was 100 rpm, and the programmed cooling was set to 1 °C / 1 min, gradually reducing the temperature from 80 °C to 25 °C. When the temperature reached 45 °C, 1.02 g of MgSO4·6H2O seed crystals were added. During the cooling process from 45 °C to 25 °C, a large amount of crystals precipitated, with a crystallization time of 12 h. After crystallization, solid-liquid separation was performed by vacuum filtration at a vacuum level of 0.070 MPa, and the solution was filtered twice. The filtered crystals are then vacuum dried at a temperature of 35°C and a pressure of 5 kPa for 15 hours until the weight is constant, thus obtaining dry crystals.

[0025] Example 3

[0026] 100.01 g of deionized water was placed in a three-necked flask and heated to 80 °C. 48.04 g of anhydrous magnesium sulfate was added, and the solution was stirred at 80 °C and 100 rpm for 10 min to dissolve, yielding a magnesium sulfate solution. The completely dissolved magnesium sulfate solution was placed in an external magnetic field, simultaneously stirred and subjected to programmed cooling. The magnetic field strength was 1500 Gs, the rotation speed was 100 rpm, and the programmed cooling was set to 1 °C / 10 min, gradually reducing the temperature from 80 °C to 25 °C. When the temperature reached 45 °C, 1.04 g of MgSO4·6H2O seed crystals were added. During the cooling process from 45 °C to 25 °C, a large amount of crystals precipitated, with a crystallization time of 12 h. After crystallization, solid-liquid separation was performed by vacuum filtration at a vacuum level of 0.068 MPa, and the solution was filtered twice. The filtered crystals are then vacuum dried at a temperature of 35°C and a pressure of 5 kPa for 15 hours until the weight is constant, thus obtaining dry crystals.

[0027] Example 4

[0028] 100.03 g of deionized water was placed in a three-necked flask and heated to 80 °C. 48.03 g of anhydrous magnesium sulfate was added, and the mixture was stirred at 80 °C and 100 rpm for 10 min to dissolve, yielding a magnesium sulfate solution. The completely dissolved magnesium sulfate solution was placed in an external magnetic field, simultaneously stirred and subjected to programmed cooling. The magnetic field strength was 1500 Gs, the rotation speed was 100 rpm, and the programmed cooling was set to 1 °C / 1 min, gradually reducing the temperature from 80 °C to 25 °C. When the temperature reached 45 °C, 1.02 g of MgSO4·6H2O granules as seed crystals were added. During the cooling process from 45 °C to 25 °C, a large amount of crystals precipitated, with a crystallization time of 12 h. After crystallization, solid-liquid separation was performed by vacuum filtration at a vacuum level of 0.075 MPa, and the mixture was filtered twice. The filtered crystals are then vacuum dried at a temperature of 35°C and a pressure of 5 kPa for 15 hours until the weight is constant, thus obtaining dry crystals.

[0029] Example 1

[0030] 100.06 g of deionized water was placed in a three-necked flask and heated to 80 °C. 48.01 g of anhydrous magnesium sulfate was added, and the mixture was stirred at 80 °C and 100 rpm for 30 min to dissolve, yielding a magnesium sulfate solution. The completely dissolved magnesium sulfate solution was then subjected to a programmed cooling process at 100 rpm, with a cooling frequency of 1 °C / 10 min, reducing the temperature from 80 °C to 25 °C. When the temperature reached 45 °C, 1.01 g of MgSO4·6H2O granules as seed crystals were added. During the cooling process from 45 °C to 25 °C, a large amount of crystals precipitated, with a crystallization time of 12 h. After crystallization, solid-liquid separation was performed by vacuum filtration at a vacuum level of 0.070 MPa, and the filtration was repeated twice. The filtered crystals were then vacuum dried at 35 °C and 5 kPa for 15 h until the weight remained constant, yielding dry crystals.

[0031] Example 2

[0032] 100.01 g of deionized water was placed in a three-necked flask and heated to 80 °C. 48.04 g of anhydrous magnesium sulfate was added, and the mixture was stirred at 80 °C and 100 rpm for 10 min to dissolve, yielding a magnesium sulfate solution. The completely dissolved magnesium sulfate solution was then subjected to a programmed cooling process at 100 rpm, with a cooling frequency of 1 °C / min, reducing the temperature from 80 °C to 25 °C. When the temperature reached 45 °C, 1.03 g of MgSO4·6H2O seed crystals were added. During the cooling process from 45 °C to 25 °C, a large amount of crystals precipitated, with a crystallization time of 12 h. After crystallization, solid-liquid separation was performed by vacuum filtration at a vacuum level of 0.075 MPa, and the filtration was repeated twice. The filtered crystals were then vacuum dried at 35 °C and 5 kPa for 15 h until the weight remained constant, yielding dry crystals.

[0033] Example 3

[0034] 100.05 g of deionized water was placed in a three-necked flask and heated to 80 °C. 48.02 g of anhydrous magnesium sulfate was added, and the mixture was stirred at 80 °C and 100 rpm for 30 min until completely dissolved, yielding a magnesium sulfate solution. The solution was transferred to a rotary evaporator, and the evaporation temperature was set to 80 °C and the vacuum degree to 0.080 MPa. The solvent was continuously evaporated until a crystalline film appeared in the solution (evaporation time approximately 180 min). After evaporation was stopped, the solution was allowed to cool naturally to 25 °C. During the cooling process, 1.02 g of MgSO4·6H2O seed crystals were added, and the solution was allowed to crystallize for 12 h. After crystallization, the wet crystals were separated by vacuum filtration (0.070 MPa, filtration twice), and then dried under vacuum at 35 °C and 5 kPa for 15 h until the weight remained constant, yielding dry crystals.

[0035] Table 1 Comparison of Experimental Data on Magnesium Sulfate Crystallization Enhanced by Magnetic Field

[0036]

[0037]

[0038] Table 2. Experimental data on the effect of magnetic field on ion migration rate, solvation energy, and crystallization activation energy.

[0039]

[0040] As shown in Tables 1 and 2, the comparison table of magnetic field-enhanced magnesium sulfate crystallization experimental data between Exemplary Examples 1-3 and Examples 1-4, as well as the experimental data tables on the effect of magnetic field on ion migration rate, solvation energy, and crystallization activation energy, shows that the magnetic field increases the concentration of Mg in the magnesium sulfate solution. 2+ With SO4 2-The magnetic field increases the migration rate of ions and induces the orderly arrangement of water molecules, reducing the solvation energy of hydrated ions. This, combined with the magnetic field effect, leads to a 40%–156% increase in the recovery rate of MgSO4·6H2O crystals; crystal purity increases from 94%–95% in traditional processes to over 99.5%; and energy consumption is reduced by 15%–22% compared to traditional evaporation crystallization. This method provides a feasible technical solution for the crystallization production of industrial-grade magnesium sulfate (especially high-purity magnesium fertilizer), possessing significant economic and environmental value.

[0041] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from its spirit or essential characteristics. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, all variations falling within the meaning and scope of equivalents of the claims are intended to be included within the present invention. No reference numerals in the claims should be construed as limiting the scope of the claims.

Claims

1. A method for enhancing magnesium sulfate crystallization using a magnetic field, characterized in that, Includes the following steps: S1: Place 100.00-110.00g of deionized water in a three-necked beaker and heat to 60-80℃. Add 40.00-50.00g of anhydrous magnesium sulfate solute and stir at 60-80℃ and 100-120r / min for 10-30min until the magnesium sulfate solute is completely dissolved to obtain a magnesium sulfate solution with a mass concentration of 28%-33%. S2: Place the completely dissolved magnesium sulfate solution obtained in S1 in an external variable magnetic field, while stirring, controlling the cooling method and the amount of seed crystals added, to promote the precipitation of magnesium sulfate as MgSO4·6H2O crystals. S3: After crystallization, the solid and liquid are filtered multiple times to obtain wet crystals, which are then dried under vacuum to obtain dry MgSO4·6H2O crystals.

2. The method for strengthening magnesium sulfate crystallization by magnetic field according to claim 1, characterized in that: In S1 and S2, the stirring methods include mechanical stirring, magnetic stirring, or ultrasonic stirring.

3. The method for strengthening magnesium sulfate crystallization by magnetic field according to claim 1, characterized in that: In S2, the strength of the external variable magnetic field is 100-3000 Gs. The magnetic field is a static magnetic field, and the magnet is made of neodymium iron boron material. The magnitude of the magnetic field is controlled by adjusting the spatial position of the N and S poles of the magnet.

4. The method for strengthening magnesium sulfate crystallization by magnetic field according to claim 1, characterized in that: In S2, the controlled cooling method adopts programmed cooling, with the cooling rate controlled at 1℃ / 10min and 1℃ / 1min respectively. The temperature is reduced from 60-80℃ to 40-45℃ through programmed cooling. At the same time, seed crystals are added and then programmed cooling is performed to 20-25℃. The total cooling time is 60-600min.

5. The method for strengthening magnesium sulfate crystallization by magnetic field according to claim 1, characterized in that: In S2, the added seed crystals are MgSO4·6H2O particles with a particle size range of 20-100 μm and a purity of over 99.5%, and the amount added is 0.5%-1% of the mass of the magnesium sulfate solution.

6. The method for strengthening magnesium sulfate crystallization by magnetic field according to claim 1, characterized in that: In S3, solid-liquid separation after crystallization is performed by vacuum filtration, with a vacuum level of 0.060–0.085 MPa, and filtration is performed 2–4 times.

7. The method for strengthening magnesium sulfate crystallization by magnetic field according to claim 1, characterized in that: In step S3, the drying process employs vacuum drying, with the drying temperature controlled at 30–45°C, the pressure controlled at 1–10 kPa, and the drying time controlled at 12–24 h, until the weight is constant and the weight loss is ≤0.1%.

8. A method for strengthening magnesium sulfate crystallization by magnetic field according to claims 1-5, characterized in that: By using a magnetic field, the amount of Mg in the magnesium sulfate solution is increased. 2+ With SO4 2- The migration rate of ions promotes the diffusion of ions to the surface of the seed crystal, and at the same time can induce the orderly arrangement of water molecules, reduce the solvation energy of hydrated ions, and reduce the crystallization activation energy by 2-10 kJ / mol. The overall energy consumption is reduced by 15%-22% compared with traditional evaporation crystallization.

9. A method for strengthening magnesium sulfate crystallization by magnetic field according to claims 1-5, characterized in that: The crystallized product is MgSO4·6H2O, with a crystal recovery rate of 35% to 64%, which is 40% to 156% higher than the theoretical recovery rate of 25% for traditional non-magnetic field crystals, and the crystal purity is ≥99.5%.